A Deixis Analysis of Song "Devide" by Ed Sheeran - Nurul Aini; Khoirunniswa Az-Zihra. T; Shella Fitri Ramadhani; Rezky Wulan Januari; Emeliya Sukma Dara (e-Journal of Linguistics, 2023)
The purpose of this research is to identify the type of Deixisand find the type of Deixis that is generally mastered in thelyrics of the song Ed Sheeran Divide. This includes the type ofqualitative research. This research uses observation method.The data collection method uses listening & analyzing the song“Divide” by Ed Sheeran. The results of this study found that alltypes of deixis were direct (68 dates ), location (4 dates), &time (1 dates). Deixis is included on the lyrics to Ed Sheeran'ssong Divide. People's deixis is often found in Ed Sheeran'sDivide lyrics. The most common types of deixis found in thisstudy were me and people deixis, such as me. The most genericplural deixis is Sie using loose 20. Deixis serves to tell the rolecontained in the lyrics. The effect of using Person Deixis is tochoose who is referred to in song lyrics. Locale deixis is used totell where or where the lyric incident took place.The effect oflocal deixis is to create the same interpretation of the locationof the incident in the song lyrics. Deixis when used in the lyricsto tell when the incident occurred. The effect according toclock deixis is to emphasize that an incident has occurred orhas already occurred.